Frailty in end-stage hip or knee osteoarthritis: validation of the Groningen Frailty Indicator (GFI) questionnaire - Meessen, Jennifer M. T. A. (Rheumatol Int, 2017)
Frailty is highly prevalent in the elderly, increasing the risk of poor health outcomes. The Groningen Frailty Indicator (GFI) is a 15-item validated questionnaire for the elderly. Its value in patients with end-stage hip or knee osteoarthritis (OA) has not yet been determined. This study assesses the validity of the GFI in this patient group. End-stage hip or knee OA patients completed the GFI (range 0–15, ≥ 4 = frail) before arthroplasty surgery. Convergent validity was determined by Spearman-rank correlation between the SF-12 physical (PCS) and mental (MCS) component scores and the physical and mental GFI-domains, respectively. Discriminant validity was assessed by means of overall GFI-score and the pain-domain of the Hip/Knee Osteoarthritis Outcome Score (HOOS/KOOS). Altogether 3275 patients were included of whom 2957 (90.3%) completed the GFI. Mean GFI-scores were 2.78 (2.41) and 2.28 (1.99) in hip and knee OA-patients, respectively, with 570 (35.9%) of hip and 344 (24.1%) of knee patients considered frail. The convergent validity was moderate to strong (physical domain R = − 0.4, mental domain R = − 0.6) and discriminant validity low (R HOOS/KOOS-pain domain = − 0.2), confirming the validity of the GFI-questionnaire in this population. With 90% of participants completing the GFI, it is a feasible and valid questionnaire to assess frailty in end-stage hip and knee OA-patients. One-third (33.3%) of the patients undergoing hip arthroplasty and a quarter (24.1%) of those undergoing knee arthroplasty are frail. Whether this is associated with worse outcomes and can thus be used as a pre-operative predictor needs to be explored.